Bovine leptospirosis: Prevalence, associated risk factors for infection and their cause-effect relation. (June 2017) - Fávero, Juscivete F.; de Araújo, Hugo L.; Lilenbaum, Walter; Machado, Gustavo; Tonin, Alexandre A.; Baldissera, Matheus D.; Stefani, Lenita M.; Da Silva, Aleksandro S.
Abstract: Leptospirosis is a cosmopolitan infectious disease that causes severe reproductive disorders in cattle, especially those related to abortion. This disease has rodents as main reservoirs; however, cattle are responsible for maintenance of the disease. Thus, the aim of this study was to identify the factors associated with infection and cause-effect relation of leptospirosis in dairy herds from Southern of Brazil. Serum samples of 1242 cows were collected from herds classified as of medium and high density, and tested by microscopic agglutination test (MAT). These farms were located in the West part of Santa Catarina State (Brazil). A total of 80 cows (6.44%) were considered positives for the infection with titration of 1:100. Using a multivariate analysis, we identified two factors associated to bovine leptospirosis: dog access to pastures (p < 0.001) and feed exposure to rodents (p = 0.05). Cause-effect analysis demonstrated that the occurrence of reproductive disorders was significantly (p = 0.01) linked to leptospirosis. Thus, we conclude that leptospirosis is prevalent in dairy cattle in the west part of Santa Catarina state, as well as the access of dogs to pastures and contact of rodents with feed increase the chance of cattle infection by Leptospira spp. Highlights: Leptospirosis is a cosmopolitan infectious disease that causes severe reproductive disorders in cattle. The presence of dogs in cattle pasture was considered associated factors for leptospirosis. The direct contact of rodents with cattle feed was identified associated factors for leptospirosis. Only 6.44% of cows were positives for the infection to Leptospira spp. Cows with reproductive problems were 8% more likely to be leptospirosis positive.